2021
DOI: 10.1017/dmp.2021.139
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rate of Patients With COVID-19 Based on Underlying Health Conditions

Abstract: Objective: To evaluate the mortality rates of 566,602 patients with coronavirus disease (COVID-19) based on sex, age, and the presence or absence of underlying diseases and determine whether the underlying disease provides prognostic information specifically related to death. Methods: The mortality rate was evaluated using conditional probability to identify the significant factors, and adjusted odds ratios (ORs) using a multivariable logistic regression analysis were estimated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Similar to other fatal coronaviruses such as the SARS-CoV and MERS-CoV (Middle East respiratory syndrome coronavirus), SARS-CoV-2 activates a cascade of undue immune responses that can lead to multi-organ failure and death [ 5 ]. However, the death rates were reportedly high in old-aged patients and patients suffering from underlying diseases conditions such as high blood pressure, diabetes, cardiovascular disease, and other respiratory diseases [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other fatal coronaviruses such as the SARS-CoV and MERS-CoV (Middle East respiratory syndrome coronavirus), SARS-CoV-2 activates a cascade of undue immune responses that can lead to multi-organ failure and death [ 5 ]. However, the death rates were reportedly high in old-aged patients and patients suffering from underlying diseases conditions such as high blood pressure, diabetes, cardiovascular disease, and other respiratory diseases [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reported mortality in pre-OMICRON COVID-19 infection for the general population with no underlying health conditions is 3%. 7 In this study, researchers reported a significant 75% reduction in mortality in the well-controlled diabetic group compared to the poorly controlled diabetes cohort with a mortality of 2.5%. In the context of lessons learnt—we need to refine our criteria for diabetic patients admitted to hospital with COVID-19 infection in the context of the decision to escalate beyond ward-based care—a history of well-controlled disease has the same prognosis as the healthy population.…”
Section: Well-controlled Diabetes Not a Contraindication For Intensiv...mentioning
confidence: 69%
“…COVID-19 patients with underlying diseases are more likely to develop critical illness and progress to death. [ 23 24 25 26 ] The Kerala population is particularly vulnerable because of high prevalence of non-communicable diseases, especially diabetes, and this was reflected in the study. [ 27 ] However, we found increasing deaths among those without any co-morbidities from the first wave to the second wave.…”
Section: Discussionmentioning
confidence: 99%